2013
DOI: 10.1038/cdd.2013.152
|View full text |Cite
|
Sign up to set email alerts
|

β-arrestin protects neurons by mediating endogenous opioid arrest of inflammatory microglia

Abstract: Microglial activation worsens neuronal loss and contributes to progressive neurological diseases like Parkinson's disease (PD). This inflammatory progression is countered by dynorphin (Dyn), the endogenous ligand of the kappa-opioid receptor (KOR). We show that microglial b-arrestin mediates the ability of Dyn/KOR to limit endotoxin-elicited production of pro-inflammatory effectors and cytokines, subsequently protecting neurons from inflammation-induced neurotoxicity. Agonist-activated KOR enhances the interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 46 publications
4
22
0
Order By: Relevance
“…We have found that Salmeterol shows similar anti-inflammatory effects on PgLPS-stimulated macrophages [115]. Additionally, Feng et al have also shown neuroprotective effects of β-arrestin2 via endogenous opioid arrest in inflammatory microglial cells [116].…”
Section: Effect Of β2-ar Agonists On Nf-κb Pathwaysupporting
confidence: 53%
“…We have found that Salmeterol shows similar anti-inflammatory effects on PgLPS-stimulated macrophages [115]. Additionally, Feng et al have also shown neuroprotective effects of β-arrestin2 via endogenous opioid arrest in inflammatory microglial cells [116].…”
Section: Effect Of β2-ar Agonists On Nf-κb Pathwaysupporting
confidence: 53%
“…The p-p38 antibody we used has been used in immunoblot analyses in previous studies, and we confirmed its specificity in California mice. Kappa opioid receptor-microglia interactions can downregulate inflammatory signaling in the brain (Feng et al, 2013), but so far the behavioral implications of these interactions have received little attention.…”
Section: Discussionmentioning
confidence: 99%
“…The increased number of double-positive cells in Arrb2 fl/fl Itgax-cre + mice suggested that the Ag-presenting and T cells priming these accumulating DCs contributed to the disease development. Discussion b-Arrestin 2 has been reported as a negative regulator of proinflammatory cytokine production, like IL-6 and TNF-a, by controlling NF-kB activation initiated by TLRs in many types of cells, such as chondrocytes, microglia, fibroblast-like synoviocytes, and splenocytes (44)(45)(46)(47). In RNA-seq, the upregulation of the genes related to positive regulation of IL-6 production and the TLR signaling pathway in Arrb2 2/2 DCs strongly supported the negative role of b-arrestin 2 in IL-6 production and also suggested that the regulation on NF-kB might be through the TLR signaling pathway.…”
Section: B-arrestin 2 Deficiency In Dcs Aggravates Sle With DC Accumumentioning
confidence: 99%